Efficacy and Tolerability of a Once Daily Formulation of Ginkgo biloba Extract EGb 761® in Alzheimer’s Disease and Vascular Dementia: Results from a Randomised Controlled Trial - Ihl, R.; Tribanek, M.; Bachinskaya, N.; null (Pharmacopsychiatry, 2012)
A 24-week randomised controlled trial was conducted to assess the efficacy of a 240 mg once-daily preparation of Ginkgo biloba extract EGb 761® in 404 outpatients≥50 years diagnosed with mild to moderate dementia (SKT 9–23), Alzheimer’s disease (AD) or vascular dementia (VaD), with neuropsychiatric features (NPI total score≥5).Separate analyses were performed for diagnostic subgroups (probable or possible AD; VaD).333 patients were diagnosed with AD and 71 with VaD. EGb 761® treatment was superior to placebo with respect to the SKT total score (drug-placebo differences: 1.7 for AD, p<0.001, and 1.4 for VaD, p<0.05) and the NPI total score (drug-placebo differences: 3.1 for AD, p<0.001 and 3.2 for VaD, p<0.05). Significant drug-placebo differences were found for most secondary outcome variables with no major differences between AD and VaD subgroups. Rates of adverse events in EGb 761® and placebo groups were essentially similar.EGb 761® improved cognitive functioning, neuropsychiatric symptoms and functional abilities in both types of dementia.
Keywords: dementia; Alzheimer’s disease; vascular dementia; Gingko biloba; EGb 761; randomised controlled trial